Prenatal diagnosis of fetal tetraphocomelia - Torres-Cepeda, Duly (2021)
Musculoskeletal defects of fetal limbs are rare. Causes of these abnormalities include amniotic band syndrome, exposure to teratogenic agents, illicit drug use, diabetes, and autosomal recessive inheritance. Tetraphocomelia is a rare congenital musculoskeletal malformation characterized by total or partial agenesis of long bones of the extremities, causing that hands and feet to arise directly from fetal trunk. Its incidence is 0.62 cases per 100,000 live births. It can occur as an isolated defect, but also can occasionally be associated with craniofacial malformations and other systemic abnormalities. Prenatal ultrasound evaluation allows early diagnosis of all fetal abnormalities, including most musculoskeletal malformations. Diagnosis should be performed carefully and interpreted with caution, since the presence of other associated systemic abnormalities should be sought. A case of prenatal diagnosis of fetal tetraphocomelia is reported.